Natural Co-Infections of Aeromonas veronii and Yellow Catfish Calicivirus (YcCV) in Ascites Disease Outbreaks in Cultured Yellow Catfish: An Emerging Fish Disease in China - Shuai Xu; Wenli Huang; Tao Zheng; Shan Jin; Zigong Wei; Bo Guan (Animals)
Yellow catfish is one of the most important aquaculture species in China, with an annual output of 565,000 tons. Between May and July 2022, the farmed yellow catfish experienced an unusually high mortality rate in an aquaculture farm next to Futou Lake in Hubei, China. Diseased fish exhibited symptoms including ascites, skin ulcers, and bleeding in the head, oral cavity, and lower jaw base. Polymerase chain reaction (PCR) and sequence analyses confirmed the co-infection of Yellow Catfish Calicivirus (YcCV) and Aeromonas veronii in the diseased fish. Transmission electron microscopy exposed abundant virus particles within kidney and spleen cells, characterized by their spherical shape and approximate diameter of 35 nm. Historically, the ascites disease in yellow catfish has been predominantly attributed to bacterial infections over the past two decades. This study represents the first documentation of a correlation between the ascites disease of yellow catfish and the natural co-infection of YcCV and Aeromonas veronii. The findings suggest a possible synergistic interaction between YcCV and bacterial pathogens, potentially aggravating disease severity in yellow catfish aquaculture.